A Metal–Organic Framework Nanosheet‐Assembled Frame Film with High Permeability and Stability. Issue 8 (25th February 2020) - Huang, Chuanhui; Liu, Cong; Chen, Xiangyu; Xue, Zhenjie; Liu, Keyan; Qiao, Xuezhi; Li, Xiao; Lu, Zhili; Zhang, Lan; Lin, Zhenyu; Wang, Tie
Abstract: The engineering of metal–organic frameworks (MOFs) into membranes and films is being investigated, to transform laboratory‐synthesized MOFs into industrially viable products for a range of attractive applications. However, rational design and construction of highly permeable MOF thin films, without trade‐offs in terms of structural mechanical stability, remains a significant challenge. Herein, a simple, general strategy is reported to prepare thin MOF nanosheet (NS)‐assembled frame film via heteroepitaxial growth from metal hydroxide film. As the thin MOF NS‐assembled film significantly enhances the permeability of mass though the film, the resultant gold nanoparticle (Au NP)@MOF film exhibits much higher catalytic efficiency than the Au NP@MOF bulk film. Meanwhile, the unique framework of the MOF NS‐assembled film resists torsion and collapse, so the composite catalyst exhibits long‐term stability. Abstract : A thin metal–organic framework nanosheet‐assembled frame (MOF NAF) film is prepared via a facile heteroepitaxial growth strategy. The thin MOF NAF film significantly enhances the permeability of the film and the unique framework structure endows the MOF NAF film with high mechanical stability.